(untitled) (Journal of Hama University, 2021)
The experience of childbirth is one of the most important and wonderful experiences that the female experiences in her life and at the same time. It is also considered one of the experiences that carries with it many problems and complications that occur,either during pregnancy or during the birth process or in the postpartum stage and these complications may have a long-term impact. There are many benefits and complications for both natural and cesarean sections. Also, self-esteem and self-confidence are among the most important constructive personality traits that an individual has, and which are considered the cornerstone of a healthy self-being. Given the cosmetic surgeries and the procedures that women try to do, to improve the body image of sport or special drugs to tighten the abdominal muscles , the extent of the high cost of material wasted in this framework, came the importance of this research in determining the impact of the method of childbirth on the body image of pregnant women.This research aims to study the effect of the method of childbirth on the body image of births at the Obstetrics and Pediatrics Hospital in Lattakia city.where the sample was chosen by the method of convenience sampling - non probability, and the sample was divided into two equal groups according to the fixed specifications of both groups. For a cesarean delivery, the second was for a normal delivery with the aim of studying the effect of each method of childbirth on the body image of women. And the criterion of the Likert triple scale rule was relied upon in analyzing the results of the arithmetic averages.The findings of this study showed that the most important of which are: Most of the women in question refuse the image of their bodies from the point of view of themselves. Negative effect of caesarean section on the women’s evaluation of their bodies ’image, either from their point of view or according to others’ opinions.In our study, we find that there is a need to spread nutritional awareness for women and the importance of their observance of nutritional instructions that they avoid gaining excess weight, which avoids problems related to poor self-esteem, which are negatively reflected in their evaluation of body image.